A Comparison of Masculinity Facial Preference Among Naturally Cycling, Pregnant, Lactating, and Post-Menopausal Women - Marcinkowska, Urszula M. (Arch Sex Behav, 2017)
Women show cyclical shifts in preferences for physical male traits. Here we investigated how fertility status influences women’s facial masculinity preference in men by analyzing a large sample of heterosexual women (N = 3720). Women were regularly either cycling (in both low- and high-conception probability groups), lactating or were currently in a non-fertile state (pregnant or post-menopausal). Analyses simultaneously controlled for women’s age and sexual openness. Participants via two alternative forced choice questions judged attractiveness of masculinized and feminized men’s faces. After controlling for the effect of age and sociosexuality, regularly cycling and pregnant women showed a stronger preference for masculinity than lactating and post-menopausal women. However, there was no significant difference in masculinity preference between women in the low- and high-conception probability groups. Women’s sociosexuality showed a positive, but very weak association with men’s facial masculinity preference. We suggest that women’s overall, long-term hormonal state (cycling, post-menopausal) is a stronger predictor of preference for sexual dimorphism than changes in hormonal levels through the cycle.